Islamisasi Ajaran Islam di Nusantara - Eza qurnia Hayati; Alimni (STAI Masjid Syuhada Yogyakarta, 2023)
Regarding the spread of Islam in Indonesia, it can be seen that the contribution of merchants from various countries can be seen from the emergence of mass organizations and Islamic communities in several important ports such as Java, Sumatra and other coastal areas. As well as evidence that many Islamic kingdoms were located along the coast, such as the kingdoms of Banten, Aceh and Demak. Aspects of the life of the kings influenced the history of the Islamization of the archipelago, which gave life to many strong cultures in the archipelago, which of course influenced the spread of Islam in the archipelago. The Great Mosque of Demak is an example of a legacy of Islamic development during the sultanate period which is still valid today. This mosque was built around 1477 M